2004
DOI: 10.1292/jvms.66.1071
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Growth Hormone (GH) Pulses in the Peripheral Circulation and GH-Releasing Hormone and Somatostatin Profiles in the Cerebrospinal Fluid of Goats

Abstract: ABSTRACT. Growth hormone (GH) is secreted in a pulsatile manner, but the underlying mechanisms of GH pulse generation remain to be resolved. In the present study, we investigated the relationship between GH pulses in the peripheral circulation and GH-releasing hormone (GHRH) and somatostatin (SRIF) profiles in the cerebrospinal fluid (CSF) of male goats. The effects of an intracerebrovent ricular (icv) injection of neuropeptide Y (NPY), galanin and ghrelin were also analyzed. Blood and CSF samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 52 publications
7
21
2
Order By: Relevance
“…GHRH, SRIF and NPY in CSF were assayed with commercial human GHRH, human SRIF and rat NPY RIA kits (RIK 8061, RIS 8001 and RIK 7180, respectively, Peninsula Laboratories, Belmont, CA, USA) according to the manufacturers' protocols using 50-μl CSF samples. Parallelism between standards for GHRH, SRIF and NPY assays and peptide levels in CSF samples has already been demonstrated in our previous studies [20,21]. The minimum assay sensitivity for GHRH was 5 pg/ml, and the intra-assay CVs for GHRH were 6.7%.…”
Section: Radioimmunoassayssupporting
confidence: 63%
See 1 more Smart Citation
“…GHRH, SRIF and NPY in CSF were assayed with commercial human GHRH, human SRIF and rat NPY RIA kits (RIK 8061, RIS 8001 and RIK 7180, respectively, Peninsula Laboratories, Belmont, CA, USA) according to the manufacturers' protocols using 50-μl CSF samples. Parallelism between standards for GHRH, SRIF and NPY assays and peptide levels in CSF samples has already been demonstrated in our previous studies [20,21]. The minimum assay sensitivity for GHRH was 5 pg/ml, and the intra-assay CVs for GHRH were 6.7%.…”
Section: Radioimmunoassayssupporting
confidence: 63%
“…These findings suggest that GHRH/SRIF interplay might be more complex than suggested by the classical hypothesis, at least in several species. We have examined the continuous profiles of several neuropeptides in cerebrospinal fluid (CSF) of the third ventricle in Shiba goats [20][21][22]. Measurement of hypothalamic neuropeptide levels, such as gonadotropin-releasing hormone levels, in the CSF of the third ventricle could be a good substitute for measurement in the portal blood [23][24][25].…”
mentioning
confidence: 99%
“…In the males, GHRH values increased in native hair and Honamlı goats after the 4th and 8th month, respectively. Considering the data of GH and GHRH together, it could be concluded that these parameters revealed parallel courses and they appear to correspond with those observed in previous studies (Mogi et al 2004, Yonezawa et al 2011). There were significant GHRP increases in Honamlı bucks and in the females of the both breeds after 4 months period.…”
Section: Discussionsupporting
confidence: 87%
“…Injections of NPY led to a suppression of GH lasting, after a delay of about 30-60 min, up to 2 h. They further established a direct link between NPY axons and SRIF neurons by receptor analysis. In the goat, which seems to have a GH profile similar to the rat but with a periodicity of w5 h, and the same effect of NPY administration was observed (Mogi et al 2004). Moreover, Pierroz et al (1996) have shown that chronic i.c.v.…”
Section: Ghrelin-npy Pathwaymentioning
confidence: 75%